1968
DOI: 10.1111/j.1600-0765.1968.tb01937.x
|View full text |Cite
|
Sign up to set email alerts
|

Electron microscopic features of chronically inflamed human gingiva

Abstract: Chronically inflamed human gingiva was studied by electron microscopy, with particular emphasis on alterations in the tissues adjacent to the gingival sulcus. In spite of dilated intercellular spaces in the crevicular epithelium recognizable bacteria remained confined to the most superficial layers of the epithelium. Such spaces did, however, contain a variety of emigrating cell types, cellular debris, lysosomes and a granular precipitate. Lysosomes were also detected in the connective tissues and were release… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
64
0

Year Published

1971
1971
2009
2009

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 171 publications
(70 citation statements)
references
References 20 publications
(10 reference statements)
6
64
0
Order By: Relevance
“…This was consistent with earlier electron microscopic studies (Freedman et al, 1968;Garant, 1976;Zoellner et al, 1989a) and indicated that this type of productive vasculopathy is not confined to the gingival sulcus and pocket wall. Vrako and Benditt (1970) studied the re-vascularization of muscle subjected to repeated freezing and repair cycles, noting that multiple layers of vascular basal lamina reflected alternate episodes of endothelial death followed by repopulation by migrating cells and it is tempting to speculate that a similar mechanism is operative in periodontitis (Zoellner and Hunter, 1989b).…”
Section: Perivascular Hyaline Materials and Vascularsupporting
confidence: 91%
“…This was consistent with earlier electron microscopic studies (Freedman et al, 1968;Garant, 1976;Zoellner et al, 1989a) and indicated that this type of productive vasculopathy is not confined to the gingival sulcus and pocket wall. Vrako and Benditt (1970) studied the re-vascularization of muscle subjected to repeated freezing and repair cycles, noting that multiple layers of vascular basal lamina reflected alternate episodes of endothelial death followed by repopulation by migrating cells and it is tempting to speculate that a similar mechanism is operative in periodontitis (Zoellner and Hunter, 1989b).…”
Section: Perivascular Hyaline Materials and Vascularsupporting
confidence: 91%
“…Free extracellular granules have also been described in inflamed connective tissue (15), wound healing sites (16), tuberculin sensitvity reactions (17), and delayed hypersensitivity and arthus reactions (18). We report the presence of two alkaline hydrolases, alkaline phosphatase and collagenase, in a welldefined cytoplasmic body characteristic of lysosomes.…”
mentioning
confidence: 69%
“…Our results provide some information about the possible mechanism of this phenomenon. The periodontal inflammation results in disruption of gingival basement membrane and stimulation ofgrowth ofjunctional epithelial cells (Freedman et al, 1968;Takarada et al, 1974). Binding of cytokines such as the various growth factors, as well as matrix molecules, to epithelial cells could result in both re-organization ofthe cell-surface receptors and altered cell behavior.…”
Section: Methodsmentioning
confidence: 99%